The Impact of Applying The Disclosure and Transparency Principle on The Financial Performance of Banks - نادر نهاد; مقديسيان سمير (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research aims to specify the impact of the disclosure and transparency principle on the financial performance of the private banks. The researcher has used the descriptive analytical method. The data collection has been based on the questionnaire, where the researcher had distributed 200 questionnaires to the CEOs, their deputies, their assistants, financial directors and internal auditors of 14 banks listed on the Damascus Stock Exchange. 190 questionnaires have been retrieved, including 15 incomplete questionnaires and 175 analyzable ones. The researcher has analyzed the data using the SPSS 20 statistical analyses program. The research has concluded that the application of disclosure and transparency effects on the financial performance of the private banks under study. The research came out with a set of recommendation the most essential of which is that enhancing the applying of the disclosure and transparency principle due to its positive role in improving the financial performance in the banks.